2011
DOI: 10.1002/jmor.10972
|View full text |Cite
|
Sign up to set email alerts
|

Histology of tooth attachment tissues and plicidentine inVaranus(Reptilia: Squamata), and a discussion of the evolution of amniote tooth attachment

Abstract: Few recent studies have examined the histological basis for tooth attachment in squamates. In the past few years, a surge of interest in this topic has led to the intriguing suggestion that the major tissues derived from the tooth germ (enamel, dentine, cementum and alveolar bone), are conservative and are present in all amniotes. In this study, we describe the histology and development of the tooth attachment complex in Varanus rudicollis, the rough-neck monitor. We provide the first published evidence for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…The evolutionary relationships of dinosaurs and crocodilians suggest that their periodontal tissues are in fact homologous. These data lend added support to a growing consensus concerning the homology of amniote tooth attachment tissues: cementum, alveolar bone, and PDL did not evolve independently in mammals and crocodilians, but are in fact plesiomorphic features of all major amniote clades and can be traced back to the base of Amniota, if not to an even more inclusive clade of tetrapods (Caldwell et al, ; Budney et al, ; Maxwell et al, ; LeBlanc and Reisz, ). Dinosauria is a highly diverse and successful clade within Amniota and these findings begin to fill in a larger gap in our understanding of dental tissue evolution across amniotes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The evolutionary relationships of dinosaurs and crocodilians suggest that their periodontal tissues are in fact homologous. These data lend added support to a growing consensus concerning the homology of amniote tooth attachment tissues: cementum, alveolar bone, and PDL did not evolve independently in mammals and crocodilians, but are in fact plesiomorphic features of all major amniote clades and can be traced back to the base of Amniota, if not to an even more inclusive clade of tetrapods (Caldwell et al, ; Budney et al, ; Maxwell et al, ; LeBlanc and Reisz, ). Dinosauria is a highly diverse and successful clade within Amniota and these findings begin to fill in a larger gap in our understanding of dental tissue evolution across amniotes.…”
Section: Discussionsupporting
confidence: 64%
“…This will help establish a baseline for comparison in future studies on dinosaur dentition by approximating the ancestral condition for the clade. Cementum, PDL, and alveolar bone may be homologous for all major amniote clades (Caldwell et al, ; Maxwell et al, ; LeBlanc and Reisz, ), but our histological examination of tooth attachment between C. bauri and A. mississippiensis suggests that the individual tissues themselves can vary greatly in different taxa, presumably to suit different functions. These differences may be diagnostic of individual taxa, but may also be phylogenetically significant.…”
Section: Discussionmentioning
confidence: 83%
“…Several authors have discovered more recently the presence of a tripartite periodontium, consisting of cementum, periodontal ligament and alveolar bone in fossil squamates and ichthyosaurs [2], [3], [8], [17]. Interestingly, recent studies of extant squamates have also shown that the stereotypically pleurodont mode of tooth implantations in Varanus and Iguana also consist of cementum and alveolar bone, albeit in different arrangements from those associated with a thecodont tooth implantation [7], [41]. These findings raise the possibility that the ability to produce the three periodontal tissues may be a synapomorphy of Amniota, or at least is a plesiomorphy for all amniote taxa that have been examined thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas many amniote taxa do not exhibit thecodonty, or a ligamentous tooth attachment (e.g. extant lepidosaurs), the alternate forms of tooth implantation are highly derived arrangements of alveolar bone and cementum [16], [41], rather than being plesiomorphic, as previously suggested [15]. The ways in which tooth implantations are defined for amniotes must be changed in order to reflect the homologies of the periodontal tissues [2], [3].…”
Section: Discussionmentioning
confidence: 99%
“…Plicidentine is currently unknown in ischnacanthiforms, and a histological analysis of the teeth would be required to determine whether these ridges are the result of infolding of the dentine in Euryacanthus. Plicidentine has been hypothesized to strengthen the attachment of the teeth to the tooth-bearing element of the jaw, particularly in active predators (Scanlon and Lee 2002;Modesto and Reisz 2008;Maxwell et al 2011aMaxwell et al , 2011bMeunier et al 2014). Euryacanthus rugosus was also one of the largest ischnacanthiform acanthodians from the Early Devonian MOTH locality, although compared with ischnacanthiforms from other localities and ages, it was a small fish.…”
Section: Discussion Trophic Niche Differentiationmentioning
confidence: 99%